A new diagnostic approach to fast-track and increase the accessibility of gastrointestinal nematode identification from faeces: FECPAKG2 egg nemabiome metabarcoding. Issue 6 (May 2022) - Francis, Emily Kate; Šlapeta, Jan
Graphical abstract: Highlights: We developed a new diagnostic approach to integrate FECPAK G2 with ITS2 nemabiome metabarcoding. A quick and simple protocol to harvest concentrated strongyle eggs utilising a repurposed pipette tip was developed. Nematode compositions from FECPAK G2 egg nemabiome metabarcoding are no different to traditional larval differentiation. Storing harvested eggs in either lysis buffer or EtOH has no impact on nematode identification for at least 60 days. Sustained nematode egg embryonation in lysis buffer leads to higher yields of DNA compared with EtOH stored nematode eggs. Abstract: Effective gastrointestinal nematode management in livestock industries is becoming increasingly difficult due to the rise of anthelmintic resistance and changes in the temporal and geographical distribution of major gastrointestinal nematodes. Underpinning the response to these challenges is the need for a fast-tracked diagnostic identification technique, making it easier for livestock producers to make informed gastrointestinal nematode management decisions. The traditional 'gold-standard' approach, larval culture followed by morphological differentiation, is laborious and potentially inaccurate. We developed a new diagnostic approach to identify gastrointestinal nematodes that integrates a remote-location digital faecal egg count platform, FECPAK G2, with internal transcribed spacer 2 (ITS2) nemabiome metabarcoding. The technique involves a quick and simple protocol to harvest concentrated strongyle eggs from the FECPAK G2 cassette utilising a repurposed pipette tip, followed by DNA isolation and Illumina next generation amplicon sequencing. The gastrointestinal nematode compositions and alpha diversity generated by our FECPAK G2 egg nemabiome metabarcoding approach was not significantly different to traditional morphological larval differentiation and nemabiome metabarcoding of larval and faecal samples. We demonstrated that storing FECPAK G2 harvested eggs in either DNA isolation lysis buffer or 80% ethanol (v/v) had no impact on gastrointestinal nematode identification outcomes for at least 60 days; enabling the transport of biological samples from their remote origins to a molecular diagnostic facility for nemabiome metabarcoding, in the absence of a cold chain. We discovered that sustained gastrointestinal nematode egg embryonation in the lysis buffer storage solution lead to higher yields of DNA compared with ethanol-stored gastrointestinal nematode eggs or faeces with gastrointestinal nematode eggs. Taking advantage of an already well-established platform such as FECPAK G2, and providing the livestock producers that use it with the option to identify gastrointestinal nematodesin their samples and contribute to large-scale gastrointestinal nematode distribution and/or anthelmintic resistance surveys, is an important future direction for the FECPAK G2 egg nemabiome metabarcoding approach.